Dialkylcarbamoyl chloride-coated versus alginate dressings after pilonidal sinus excision: a randomized clinical trial (SORKYSA study). Issue 2 (4th February 2020) - Romain, B; Mielcarek, M; Delhorme, J B; Meyer, N; Brigand, C; Rohr, S; Chilintseva, N; Knepfler, T; Manfredelli, S; Simeu, B; Tréchot, B; Triki, E; et al.
Abstract: Background: Disease of the pilonidal sinus is a common condition that affects mainly young adults. Options for management include excision of the sinus tracts, leaving the wound open to heal by secondary intention. The aim of this study was to compare wound healing with dialkylcarbamoyl chloride (DACC)-coated dressings versus alginate dressings. Methods: This multicentre trial randomized consecutive patients undergoing surgery for pilonidal disease to postoperative wound care with either DACC-coated or alginate dressings. The primary outcome was the proportion of wounds healed after 75 days. Secondary outcomes were the local status of wounds during the healing process, the quality assessment of the dressings by the patient, and the time needed to return to usual activities. Results: A total of 246 patients were included: 120 in the DACC-coated group and 126 in the alginate group. In per-protocol analysis, there were significantly more patients with completely healed wounds after 75 days in the DACC group than in the alginate group: 78 of 103 (75·7 per cent) versus 58 of 97 (60 per cent) respectively (odds ratio 2·55, 95 per cent c.i. 1·12 to 5·92; P  = 0·023). During follow-up, wounds with alginate dressings had more fibrin than those with DACC-coated dressings, but the difference was not significant ( P  = 0·079). There was no difference between the two arms in patients' assessment of the dressings. Conclusion: The number of wounds completely healed at 75 days was significantly higher for DACC-coated compared with alginate dressings. However, the preplanned, clinically significant improvement in healing of 20 per cent was not reached. Registration number: NCT02011802 (https://clinicaltrials.gov/ ). Graphical Abstract: This multicentre RCT compared the efficacy of dialkylcarbamoyl chloride (DACC)-coated dressings with alginate dressings for wound healing after pilonidal sinus excision. In per-protocol analysis, significantly more patients had completely healed wounds at 75 days in the DACC group than in the alginate group: 78 of 103 (75·7 per cent) versus 58 of 97 (60 per cent) respectively (odds ratio 2·55, 95 per cent c.i. 1·12 to 5·92; P  = 0·023). No clinically important difference